(untitled) - Boisserie, Etienne (Romanica Olomucensia, 2012)
This paper contains some reflexions on the difficulty to conceive the stranger in the Central Europe, presenting, in particular, the case of Slovakia in the first decades of the 20th century.
Keywords: Slovakia; Hungarian kingdom; First World War; Slovaks-Hungarians (mutual relations).